The contribution of feeding mode to obesogenic growth trajectories in American Samoan infants - Hawley, Nicola L (2013)
BACKGROUND: Samoans are recognized for their particularly high body mass index and prevalent adult obesity but infants are understudied. OBJECTIVE: To examine the prevalence of overweight and obesity and determine the contribution of feeding mode to obesogenic growth trajectories in American Samoan infants. METHODS: Data were extracted from the well baby records of 795 (n=417 male) Samoan infants aged 0-15 months. Mixed-effects growth models were used to produce individual weight and length curves. Further mixed-effects models were fitted with feeding mode (breastfed, formula- or mixed-fed) as a single observation at age four (±2) months. Weight and length values were converted to Z-scores according to the CDC 2000 reference. RESULTS: At 15 months, 23.3% of boys and 16.7% of girls were obese (weight-for-length > 95th percentile). Feeding mode had a significant effect on weight and length trajectories. Formula-fed infants gained weight and length faster than breastfed infants. Formula-fed boys were significantly more likely to be obese at 15 months (38.6%) than breastfed boys (23.4%), χ2=8.4, P<0.01, odds ratio=2.05, 95% CI [1.04, 4.05]. CONCLUSION: Obesity in American Samoans is not confined to adults. Obesity prevention efforts should be targeted at early life and promotion of breastfeeding may be a suitable intervention target.